2016
DOI: 10.1128/msphere.00189-16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pathogenicity of United Kingdom Isolates of the Emerging Pathogen Candida auris and Other Key Pathogenic Candida Species

Abstract: The incidence of invasive candidiasis, which includes candidemia and deep tissue infections, continues to rise and is associated with considerable mortality rates. Candida albicans remains the most common cause of invasive candidiasis, although the prevalence of non-albicans species has increased over recent years. Since its first description in 2009, Candida auris has emerged as a serious nosocomial health risk, with widespread outbreaks in numerous hospitals worldwide. However, despite receiving considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
421
3
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(465 citation statements)
references
References 25 publications
32
421
3
9
Order By: Relevance
“…These findings are in agreement with those of recent studies from other investigators, who also reported that C. auris isolates were generally resistant or less susceptible to azoles but susceptible to echinocandins (26, 8, 9, 13, 14, 16). Our finding that amphotericin B demonstrated less activity against C.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in agreement with those of recent studies from other investigators, who also reported that C. auris isolates were generally resistant or less susceptible to azoles but susceptible to echinocandins (26, 8, 9, 13, 14, 16). Our finding that amphotericin B demonstrated less activity against C.…”
Section: Discussionsupporting
confidence: 93%
“…albicans, suggesting that this emerging species is not as virulent as the latter species. Borman et al (8) attempted to address the virulence of C. auris by using a Galleria mellonella larva model.…”
Section: Discussionmentioning
confidence: 99%
“…auris accounted for >5% of candidemia in a national ICUs survey and up to 30% of candidemia at individual hospitals in India [4, 19]. In the subsequent 2 years, several reports of hospital-associated infections emerged from South Africa, United Kingdom, Venezuela, Colombia, United States, Pakistan, Israel, Kenya, and Spain [7, 1118, 24]. Table 1 lists several countries reporting C .…”
Section: The Past and Present Of C Auris: Is The Emergence Of C Aurmentioning
confidence: 99%
“…However, another study using the Bruker RUO system revealed direct on‐plate extractions resulted in low score matches for 50% of strains and the remaining 50% were unidentified . Partial extraction methods are reported by others to give reliable identification . Local experience indicates that at least partial extractions are required to consistently achieve log scores of ≥2.00 (authors: personal communication).…”
Section: Laboratory Diagnosismentioning
confidence: 99%